Influence of environmental integrity on the reproductive biology of Astyanax altiparanae Garutti & Britski, 2000 in the Ivinhema river basin - Lucilene Finoto Viana; Karina Keyla Tondato; Yzel Rondon Súarez; Sidnei Eduardo Lima-Junior (Acta Scientiarum. Biological Sciences, 2014)
In this study, it was examined the reproductive biology of Astyanax. altiparanae, in streams with different levels of environmental disturbance in the Ivinhema river basin (Mato Grosso do Sul State, Brazil). Samplings were conducted between July 2001 and November 2011, at 101 sites, using sieves, seining nets, gill nets and electrofishing. Streams were classified into three levels of environmental integrity. We analyzed 735 specimens, 410 females and 325 males. Females predominated in impacted streams and both sexes presented nearly the same pattern of length distribution in the three levels of environmental integrity. Females reached gonadal maturity with greater lengths (L50 = 55.67mm) in altered and impacted streams and had higher reproductive activity between October and December. The species showed higher Condition Factor and higher reproductive intensity in the impacted streams. Our results evidenced that in impacted sites the species exhibited a good ability to allocate a significant portion of its energy to reproduction, probably due to the greater supply of food.